Simulation as a teaching method for nursing education in healthcare-associated infection prevention and control in Asian countries: a qualitative study - Thi Thu Hien, Do (2024)
Background: Applying simulation for nursing education, especially in healthcare-associated infection prevention and control (HAI-PC) in developing countries has limited evidence. The study was conducted to explore educators’ perceptions of simulation as a teaching method for nursing education in HAI-PC in two Vietnamese and two Cambodian universities. Methods: An exploratory qualitative design was applied. A focus group of 37 educators from four universities was conducted for data collection. Inductive and deductive qualitative content analysis was applied in analysing the data. Results: The core category was constructed to reflect educators’ perception of scenario-based simulation (SBS) as a teaching method for nursing education in HAI prevention and control. This main category included three subcategories: (i) enhancing nursing competence; (ii) preparing students for simulation; and [1] promoting simulation pedagogy competence. Conclusions: The findings identified the importance and benefits of applying simulation as a teaching method in nursing education. Additionally, it emphasized the necessity of enhancing knowledge associated with HAIs and providing additional training on simulation for educators to improve the quality of conducting simulations.